National Survey of DNA Crime Laboratories, 1998 ([Verlag nicht ermittelbar], 2000)
This study reports findings from a survey of publicly operated forensic crime labs that perform deoxyribonucleic acid (DNA) testing. The survey includes questions about each lab's budget, personnel, workload, and operating policies and procedures. Data were obtained from 108 out of 120 estimated known labs, including all statewide labs.